1978
DOI: 10.1002/ana.410030416
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypothermia on the human brainstem auditory response

Abstract: Latency measurements between three potentials (waves I, III, and IV/V) of the human brainstem auditory response can allow early detection of certain posterior fossa lesions. The diagnostic use of these interwave latencies requires knowledge of what factors may prolong them in the absence of disease. Hypothermia appears to be one such factor--in 5 neurologically and audiometrically normal patients, mean esophageal temperatures as high as 34.5 degrees C resulted in prolongations of central auditory conduction ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
6

Year Published

1983
1983
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(49 citation statements)
references
References 1 publication
2
40
0
6
Order By: Relevance
“…Kawakami (1981) also reported the latency prolongation of ABR in case of thiopental anesthesia in human. The effect of hypothermia upon waves III and V were reported by Stockard et al (1978) and Kaga et al (1979). The resuts obtained in the present study are in agreement with their results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Kawakami (1981) also reported the latency prolongation of ABR in case of thiopental anesthesia in human. The effect of hypothermia upon waves III and V were reported by Stockard et al (1978) and Kaga et al (1979). The resuts obtained in the present study are in agreement with their results.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it is conceivable that the responses evoked in the auditory tract are also influenced by temperature. The effect of hypothermia upon auditory evoked brainstem response (ABR) was reported by Stockard et al (1978) and Kaga et al (1979). Electrocochleographical studies in human, however, have not been reported, although several animal experiments on cochlear potentials have been reported since 1950.…”
mentioning
confidence: 99%
“…The measurement of BAEPs has been used to monitor neuronal function at the level of the brainstem. Hypothermia increases the BAEP interwave latencies (5,11,12). BAEP components have also been reported to be abolished at temperatures below 20°C (12).…”
mentioning
confidence: 97%
“…An increase in body temperature leads to an increase in neural conduction speed and a reduction in ABR latency (Stockard et al 1978;Markand et al 1987). Therefore, it is important to account for any change in temperature in serially recorded ABR data.…”
Section: Mechanisms Mediating Rapid Reduction In Abr Latency Post-udmentioning
confidence: 99%